Genetic Basis and Molecular Mechanisms of Uveal Melanoma Metastasis: A Focus on Prognosis - Gallenga, Carla Enrica; Franco, Elena; Adamo, Ginevra Giovanna; Violanti, Sara Silvia; Tassinari, Paolo; Tognon, Mauro; Perri, Paolo (Frontiers in Oncology, 2022)
Uveal melanoma (UM) is the most frequently found primary intraocular tumor, although it accounts for only 5% of all melanomas. Despite novel systemic therapies, patient survival has remained poor. Indeed, almost half of UM patients develop metastases from micro-metastases which were undetectable at diagnosis. Genetic analysis is crucial for metastatic risk prediction, as well as for patient management and follow-up. Several prognostic parameters have been explored, including tumor location, basal dimension and thickness, histopathologic cell type, vascular mimicry patterns, and infiltrating lymphocytes. Herein, the Authors review the available literature concerning cytogenetic prognostic markers and biochemical pathways correlated to UM metastasis development.